Enhancing Sustainable Behavior in Waste Management: A Social Perspective - Siti Khatijah, Zamhari; Ahmad Fariz, Mohamed; Azahan, Awang (Springer, Singapore, 2025)
Household waste management is considered as part of the municipal waste where it contributes to a large amount to municipal solid waste (MSW). It is crucial to identify the existing waste management behavior of the household to make adjustment and process improvement to achieve sustainable waste management. Therefore, the objective of this study is to examine the behavior and factors that influence community behavior in managing household waste in rural areas particularly in Kampung Sungai Midin, Kuching, Sarawak. The study focuses on physical environment as well as social and cultural aspects. This study employed both quantitative and qualitative approach. Quantitative data were collected by using questionnaire and analyzed using IBM SPSS Version 24.0 while qualitative data were collected through face-to-face structured interviews, semi-structured interview, and observation. These interviews were transcribed and analyzed using thematic analysis. The survey method involved 75 respondents, selected based on convenience sampling method. The findings show that respondents’ behavior was highly influenced by physical environment (57.6%) and moderately influenced by social and cultural aspects (42.4%). The physical features of the river as well as the condition and characteristics of some houses built on stilts along the riverbank could be seen as a means of easing the household waste. Furthermore, lack of facilities is one of the barriers that hinders them from practicing waste segregation and recycling. Low social interaction affects the intention of community to engage in sustainable solid waste management.